Determining Factors that Influence The Profits of Sharia Life Insurance Companies Registered with The Financial Services Authority for The 2018-2022 Period - Alfiani Andari; Sunarsih (International Journal of Islamic Finance, 2024)
Background: The Islamic finance industry in Indonesia, especially the Islamic insurance industry, is experiencing rapid growth. In accordance with the development of Indonesia's sharia finance reported in 2022, the total sharia insurance assets in 2022 were recorded at 45,025 trillion, of which the largest total assets were sourced from sharia life insurance worth 34,891 trillion. Thus, it can be said that sharia general insurance and reinsurance companies. However, the net profit of sharia life insurance has actually decreased in several years. Objectives: This research aims to examine the effect of premium growth ratio, investment returns, underwriting results, risk based capital, and liquidity on the profits of Sharia Life Insurance companies registered with the Financial Services Authority (OJK) for the 2018-2022 period. Novelty: With the existence of research gaps in previous studies, the authors feel the need to conduct this study as a form of re-examining related independent variables, considering the inconsistent results of previous studies. Research Methodology / Design: Sample selection used a purposive sampling method which resulted in a sample of 21 Sharia Life Insurance companies with a total of 105 financial report data. This type of research is quantitative research. Data collection was carried out through secondary data, namely the company's annual report. The analytical method used in this research is panel data regression analysis which is measured using STATA 17 software. The best analysis model chosen in the research is the fixed effect mode. Findings: The research results show that the variables of investment returns and underwriting results have a positive and significant effect on company profits. Meanwhile, the liquidity variable has a negative and significant effect on company profits. Then, the premium growth ratio and risk based capital variables have no effect on company profits. Implication:. It is necessary to add samples and develop them, not only using sharia life insurance companies, but can take examples of sharia general insurance or sharia reinsurance. Further research may also add more variables that could potentially affect profits. The short research deadline, only five years, indicates the need for further research with a wider time span to obtain more precise and accurate results. In addition, further development of this theory is needed to strengthen the research findings